2014
DOI: 10.1128/mcb.01045-13
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Enhancer Selection Confers Alternate Modes of Notch Regulation on argos

Abstract: Wiring between signaling pathways differs according to context, as exemplified by interactions between Notch and epidermal growth factor receptor (EGFR) pathways, which are cooperative in some contexts but antagonistic in others. To investigate mechanisms that underlie different modes of cross talk, we have focused on argos, an EGFR pathway regulator in Drosophila melanogaster which is upregulated by Notch in adult muscle progenitors but is repressed in the wing. Results show that the alternate modes of cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Further investigation into the regulation of argos by Notch in these two contexts demonstrated that different enhancer sequences are used in each tissue. One mediates direct activation of argos by Su(H) in the AMPs, whereas the other mediates its indirect repression via HLHmβ [14], a direct target of Notch signaling in the wing pouch. These results suggest that enhancers are selected based on the expression of tissue-specific transcription factors that modulate enhancer accessibility.…”
Section: Signaling Context and Cellular History Generate Diversity Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation into the regulation of argos by Notch in these two contexts demonstrated that different enhancer sequences are used in each tissue. One mediates direct activation of argos by Su(H) in the AMPs, whereas the other mediates its indirect repression via HLHmβ [14], a direct target of Notch signaling in the wing pouch. These results suggest that enhancers are selected based on the expression of tissue-specific transcription factors that modulate enhancer accessibility.…”
Section: Signaling Context and Cellular History Generate Diversity Inmentioning
confidence: 99%
“…These results suggest that enhancers are selected based on the expression of tissue-specific transcription factors that modulate enhancer accessibility. In cultured cells derived from the AMPs, expression of the transcription factor Twist is required for Su(H) binding to the relevant argos enhancer, and over-expression of Twist in the wing pouch can convert the regulation of argos downstream of Notch from repression to activation [14,15]. A similar factor (Vvl) was identified that may play a role analogous to that of Twist in regulating enhancer activity in the wing pouch [14].…”
Section: Signaling Context and Cellular History Generate Diversity Inmentioning
confidence: 99%
“…Based on previous reports in Drosophila, the effect of Notch signaling on aos expression is context dependent (Housden et al, 2014). Gene expression is often controlled by multiple cisregulatory units that integrate information from various transcriptional inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, aos has been reported to exhibit context-dependent enhancer selection in the wing: aos contains three enhancer regions identified, that are differentially responsive to factors that act downstream of Notch or EGFR signaling pathways (Ajuria et al, 2011;Krejci et al, 2009). The presence of context-determining factors will determine whether an enhancer is primed to react to a specific signal, which may result in a gene having different responses towards the same signals depending on which enhancer is accessible (Housden et al, 2014). Notably, the aos1-GFP reporter experiment reported here, and the Su(H) ChIP data, argue that the aos1 enhancer is directly responsive to Notch signaling in R4, indicating that Notch activates aos expression in this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation